Densification and coarsening of SnO2-based materials containing manganese oxide - Gouvea, D.; Smith, A.; Bonnet, J. P.; Varela, José Arana [UNESP] (Elsevier B.V., 1998)
The present work presents results on natural sintering of tin dioxide ceramics, prepared by a chemical route or by conventional mixing and containing manganese (X-Mn = Mn/(Mn + Sn)(atomic) with 0 less than or equal to X(Mn)less than or equal to 0.15). This cation, which is practically insoluble in SnO2 network, stays at the grain surface. During thermal treatment (500 degrees C less than or equal to T-s less than or equal to 1400 degrees C), as long as the manganese surface concentration is lower than a critical value, equal to 5.10(-6) mol m(-2), no densification takes place. As soon as this value is reached, densification and grain growth occur simultaneously. The shrinkage kinetics is fast and high rho/rho(t) values can be obtained (for example. rho/rho(t)=0.95 for T-s=1300 degrees C and X-Mn=0.004). The dependence between manganese content, manganese distribution, grain size and sintering behaviour is also discussed. (C) 1998 Published by Elsevier B.V. Limited.